«What the nation would not do, a woman did»: Lady Franklin e l’esplorazione artica - Brazzelli, Nicoletta (Ledizioni, 2022)
In February 1845 Sir John Franklin was given the command of a naval expedition to find a Northwest Passage in Canada and he set sail on the Erebus, with a three-year supply of provisions: when, in 1848, the expedition had not returned, Lady Jane Franklin was personally involved in the organization of several search parties. Although she never participated in any of these, she took charge of their preparation and scheduling. Finally, in 1857 she sent the Fox on a final search for survivors: three years later, Francis Leopold McClintock returned with evidence of the expedition’s unhappy fate. In this essay, the tragic loss of Sir John Franklin’s expedition in search of the Northwest Passage is investigated from the perspective of Franklin’s wife, who won significant popular celebrity through her efforts to discover the fate of her beloved husband. Jane Franklin greatly transformed the narrative discourse of Arctic exploration, both through the direct influence she exerted on the search for Franklin and through her rewriting of the language of heroism, suffering and national honour. Her correspondence with British prime ministers, Members of Parliament, Lords of the Admiralty offers a private side to a national tragedy and sheds new light on what Sir John Franklin’s disappearance meant to England and its public opinion. The analysis of Lady Franklin’s letters focuses on the combination of the (female) language of affection to promote (male) imperial views. These letters persuaded the Admiralty to persevere with the search when it would have given up, and kept Franklin’s memory and honour alive in the national imagination. The sequence of Jane’s letters also traces the progression of Lady Franklin’s growing awareness of her husband’s death and contributes to the transformation of the Arctic explorer into a heroic figure. The language of Lady Franklin’s letters is geographically precise and conveys detailed information on the Arctic, whilst also providing readers with the domestic side of the disaster. She is the ...